2017
DOI: 10.1111/jpc.13742
|View full text |Cite
|
Sign up to set email alerts
|

Pulse oximetry values of neonates admitted for care and receiving routine oxygen therapy at a resource‐limited hospital in Kenya

Abstract: AimThere are 2.7 million neonatal deaths annually, 75% of which occur in sub‐Saharan Africa and South Asia. Effective treatment of hypoxaemia through tailored oxygen therapy could reduce neonatal mortality and prevent oxygen toxicity.MethodsWe undertook a two‐part prospective study of neonates admitted to a neonatal unit in Nairobi, Kenya, between January and December 2015. We determined the prevalence of hypoxaemia and explored associations of clinical risk factors and signs of respiratory distress with hypox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Our data show higher hypoxaemia prevalence in other conditions than most studies in the 2009 hypoxaemia review and more recent studies (malaria 8.5% versus 2.9–17.1%, meningitis 17.1 vs 2.7–14.6, malnutrition 16.3 vs 1.8–8.3, seizures 14.3 vs 11.8, diarrhoea 6.1 vs 0–4.7) [2,[8], [9], [10], [11], [12], [13], [14], [15]], but similar results to a major tertiary hospital in the same region of Nigeria [8,9]. Our data show hypoxaemia prevalence among neonates is high (22%), with similar overall rates to other studies from Africa (17–41%) [2,9,10,14,15] and particularly high prevalence among preterm neonates (27%) and those with neonatal encephalopathy (33%).…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…Our data show higher hypoxaemia prevalence in other conditions than most studies in the 2009 hypoxaemia review and more recent studies (malaria 8.5% versus 2.9–17.1%, meningitis 17.1 vs 2.7–14.6, malnutrition 16.3 vs 1.8–8.3, seizures 14.3 vs 11.8, diarrhoea 6.1 vs 0–4.7) [2,[8], [9], [10], [11], [12], [13], [14], [15]], but similar results to a major tertiary hospital in the same region of Nigeria [8,9]. Our data show hypoxaemia prevalence among neonates is high (22%), with similar overall rates to other studies from Africa (17–41%) [2,9,10,14,15] and particularly high prevalence among preterm neonates (27%) and those with neonatal encephalopathy (33%).…”
Section: Discussionsupporting
confidence: 42%
“…While hypoxaemia is less well studied in non-pneumonia cohorts, the available data suggests that hypoxaemia may be common in many non-respiratory conditions [2,[8], [9], [10], [11], [12], [13], [14], [15], [16], [17]], and that addressing oxygen access issues for these populations could deliver substantial mortality reductions [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, some of these interventions also carry a risk of harm when administered by inadequately trained staff or without proper equipment. For example, provision of oxygen therapy in the absence of pulse oximetry monitoring increases the risk of retinopathy and subsequent visual impairment in preterm neonates [ 8 , 9 ]. Although an estimated 72% of deliveries globally occurred in facilities from 2012 to 2017 [ 10 ], lack of access to delivery and postnatal care remains a challenge in LMICs [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen targeting in our study was expectedly poorer than these studies, which were conducted in well-resourced settings using continuous pulse oximetry monitoring by dedicated neonatal intensive care nurses. Data from Kenya involving intermittent SpO 2 monitoring found that in the first 24 hours of life, only 6.7% of preterm/low birthweight neonates remained consistently within the target SpO 2 range, and more than half (53%) had more SpO 2 readings outside the target range than within 29…”
Section: Discussionmentioning
confidence: 99%
“…Data from Kenya involving intermittent SpO 2 monitoring found that in the first 24 hours of life, only 6.7% of preterm/low birthweight neonates remained consistently within the target SpO 2 range, and more than half (53%) had more SpO 2 readings outside the target range than within. 29 …”
Section: Discussionmentioning
confidence: 99%